Balloon Valvuloplasty for Congenital Aortic Stenosis: Experience at a Tertiary Center in a Developing Country - Fatme A. Charafeddine; Haytham Bou Houssein; Nadine B. Kibbi; Issam M. El-Rassi; Anas M. Tabbakh; Mohammad S. Abutaqa; Ziad F. Bulbul; Nour K. Younis; Mariam T. Arabi; Fadi F. Bitar (Journal of Interventional Cardiology)
Background. Aortic valve stenosis accounts for 3–6% of congenital heart disease. Balloon aortic valvuloplasty (BAV) is the preferred therapeutic intervention in many centers. However, most of the reported data are from developed countries. Materials and Methods. We performed a retrospective single-center study involving consecutive eligible neonates and infants with congenital aortic stenosis admitted for percutaneous BAV between January 2005 and January 2016 to our tertiary center. We evaluated the short- and mid-term outcomes associated with the use of BAV as a treatment for congenital aortic stenosis (CAS) at a tertiary center in a developing country. Similarly, we compared these outcomes to those reported in developed countries. Results. During the study period, a total of thirty patients, newborns (n = 15) and infants/children (n = 15), underwent BAV. Left ventricular systolic dysfunction was present in 56% of the patients. Isolated AS was present in 19 patients (63%). Associated anomalies were present in 11 patients (37%): seven (21%) had coarctation of the aorta, two (6%) had restrictive ventricular septal defects, one had mild Ebstein anomaly, one had Shone’s syndrome, and one had cleft mitral valve. BAV was not associated with perioperative or immediate postoperative mortality. Immediately following the valvuloplasty, a more than mild aortic regurgitation was noted only in two patients (7%). A none-to-mild aortic regurgitation was noted in the remaining 93%. One patient died three months after the procedure. At a mean follow-up of 7 years, twenty patients (69%) had more than mild aortic regurgitation, and four patients (13%) required surgical intervention. Kaplan–Meier freedom from aortic valve reintervention was 97% at 1 year and 87% at 10 years of follow-up. Conclusion. Based on outcomes encountered at a tertiary center in a developing country, BAV is an effective and safe modality associated with low complication rates comparable to those reported in developed countries.